2018
DOI: 10.1111/1440-1681.12992
|View full text |Cite
|
Sign up to set email alerts
|

Co‐expression of LAG3 and TIM3 identifies a potent Treg population that suppresses macrophage functions in colorectal cancer patients

Abstract: Regulatory T (Treg) cells are critical suppressors of inflammation and are thought to exert mainly deleterious effects in cancers. In colorectal cancer (CRC), Foxp3 Treg accumulation in tumors was associated with poor prognosis. Hence, we examined the circulating Treg cells in CRC patients. Compared to controls, CRC patients presented mild upregulations in CD4 CD25 T cells and in the more canonical CD4 CD25 Foxp3 Treg cells in peripheral blood mononuclear cells. Both of these Treg populations could be roughly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…On activated Treg, LAG-3 expression becomes upregulated facilitating robust interaction with MHC II on DCs, further promoting suppression of the anti-tumor response in the TME (94). LAG-3+CD4+CD25+ Treg isolated from colorectal cancer patients secrete high levels of immunosuppressive cytokines including TGFβ and IL-10, thereby maintaining the immunosuppressive milieu (95). Camisaschi et al describe a population of CD4+CD25+FoxP3+ T cells expressing LAG-3 with increased presence in peripheral circulation and solid tumor in advanced stage melanoma and colorectal cancers.…”
Section: Mechanisms Of Treg-mediated Suppression In the Tumor Microenmentioning
confidence: 99%
“…On activated Treg, LAG-3 expression becomes upregulated facilitating robust interaction with MHC II on DCs, further promoting suppression of the anti-tumor response in the TME (94). LAG-3+CD4+CD25+ Treg isolated from colorectal cancer patients secrete high levels of immunosuppressive cytokines including TGFβ and IL-10, thereby maintaining the immunosuppressive milieu (95). Camisaschi et al describe a population of CD4+CD25+FoxP3+ T cells expressing LAG-3 with increased presence in peripheral circulation and solid tumor in advanced stage melanoma and colorectal cancers.…”
Section: Mechanisms Of Treg-mediated Suppression In the Tumor Microenmentioning
confidence: 99%
“…Similarly, aiming to induce immunosuppression, Treg cells have been associated with tumor progression during CRC ( Figure 2 ) [ 49 ]. Interestingly, CRC patients display Treg cells with a higher expression of several molecules that correlate with suppression, such as Tim-3, LAG-3, TGF-β, IL-10, CD25, and CTLA-4 [ 50 ], and by the BLIMP-1 transcription factor expression in the tumor [ 51 ]. The infiltration of Treg cells into the colon is significantly higher in CRC than in a healthy colon, as well as in patients with limited disease (Union for International Cancer Control (UICC) criteria I and II) than in metastatic (UICC criteria III and IV) ones [ 52 ].…”
Section: Treg Cells During Crc In Clinical Cases: An Overviewmentioning
confidence: 99%
“…25,26 For ischemia-reperfusion injury, Treg transplantation can significantly reduce infiltration of macrophages and lymphocytes into ischemic tissue and can inhibit apoptosis. 27,28 Our results showed that the proportion of Tregs was significantly decreased in LIRI mice, suggesting that the inflammatory response was activated in these mice. Excessive inflammation can cause further damage to lung tissues.…”
Section: Discussionmentioning
confidence: 67%